INTEGRATION OF ARTIFICIAL INTELLIGENCE INTO STRATEGIC MANAGEMENT PROCESSES FOR ACHIEVING SUSTAINABLE ENTERPRISE DEVELOPMENT - Zabranskyi , Maksym; Semenchuk , Tetiana (Collection of scientific papers «ΛΌГOΣ», 2025)
Artificial Intelligence (AI) is becoming a pivotal tool in the strategic management of modern enterprises, enabling them to adapt to rapidly changing market conditions. The integration of AI into management processes facilitates decision optimization and efficiency as well as opens new opportunities for sustainable company development. The use of AI allows enterprises to analyze data deeply, forecast trends, and automate complex processes, which is crucial for maintaining competitiveness in the long term [1].